Differential response of neurons to autophagy modulation in Huntington’s disease - Ankit Sharma; Sushma Rao; Ravi Manjithaya; Vasu Sheeba (Autophagy Reports)
Huntington’s disease (HD) is caused by the expansion of poly-glutamine repeats in the Huntingtin (Htt) gene and is associated with a wide variety of motor and physiological (sleep, metabolism, etc.) perturbations. Studies from diverse model organisms have proposed that modulation of autophagy (a key protein homeostatic pathway) can mitigate the toxic effects of mutant HTT protein. However, consistent changes are not observed across studies, and the improvements in phenotypes can be associated with changes in specific circuits/neurons affected by the mutant HTT protein. They suggest that not all neurons respond effectively to autophagy modulation. Hence, it remains to be understood whether diverse circuits/neurons affected by mutant HTT protein respond effectively to this intervention. Using a genetic approach, we expressed mutant HTT protein independently in diverse sets of neurons in male Drosophila melanogaster and asked whether genetic modulation of autophagy pathway through Atg8a overexpression can mitigate the toxic effect of mutant HTT protein. We found that in male flies, not all neurons/circuits expressing mutant HTT protein respond effectively to ATG8a protein. Circadian neurons and neurons regulating carbohydrate and lipid metabolism (Dilp2+ve) showed improvement, while motor and neurons responding to temperature changes showed no improvement. Using cellular markers we also showed that these phenotypes can be attributed to specific changes in mutant HTT and Ref(2)P proteins (autophagy marker). Our study suggests that not all circuits respond effectively to autophagy modulation and suggests a potential cause for low success of autophagy modulators in clinical trials..